PENGARUH PENGENDALIAN DIRI DAN PERILAKU PEMBAYARAN DIGITAL TERHADAP EFEKTIVITAS PENGELOLAAN UANG SAKU MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2025 UNIVERSITAS JAMBI - Cici Mikha Theovani Simanjuntak; Fachruddiansyah Muslim; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to investigate the influence of self-control and digital payment behavior on the effectiveness of allowance management among Economics Education students at Universitas Jambi. The growing development of digital financial technology has encouraged students to use various digital payment services, including e-wallets, mobile banking, and QRIS, in their daily transactions. Although these services offer practical and efficient transaction methods, their use may also increase spending tendencies if not balanced with adequate self-control. This research employed a quantitative approach with an explanatory research design. The population consisted of Economics Education students from the 2025 cohort at Universitas Jambi, and 97 students who actively used digital payment services were selected as research respondents through the total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistical analysis, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The findings show that self-control has a positive and significant effect on the effectiveness of allowance management. Digital payment behavior was also found to positively and significantly affect the effectiveness of allowance management. In addition, both variables simultaneously demonstrated a positive and significant influence on the effectiveness of allowance management. These findings imply that students who are able to regulate their behavior and use digital payment services responsibly tend to manage their financial resources more effectively. Therefore, strengthening self-control and encouraging responsible digital payment practices are essential to supporting effective financial management among university students in the digital era.